Kreacja mniejszości narodowościowych i problem identyfikacji jednostki – Grenki med Andreja Skubica - Wojtoń, Regina (Slavia Centralis, 2020)
The creation of national minorities and the problem of individual identity - Andrej Skubic's Grenki medThe main subject of this paper is the presentation of national minorities in Andrej Skubic’s novel Grenki med/Bitter Honey, and an attempt to identify the novel’s true hero. In times of globalization, fiction deals with these problems as well. In order to achieve their aims, authors imagine a world, placing in it main characters which can be analyzed from various perspectives. Having problems with their own identity, the characters in the novel are unable to determine their social and national affiliations.
Keywords: generation; globalization; migration; novel; Andrej Skubic; Grenki med